Intron retention is among six unreported AGL mutations identified in Malaysian GSD III patients - Abdullah, Ili Syazwana; Teh, Ser Huy; Khaidizar, Fiqri Dizar; Ngu, Lock Hock; Keng, Wee Teik; Yap, Sufin; Mohamed, Zulqarnain (Springer Verlag (Germany), 2019)
Background: Glycogen storage disease type III is an autosomal recessive disorder that is caused by deficiencies of the glycogen debranching enzyme. Mutations within the AGL gene have been found to be heterogeneous, with some common mutations being reported in certain populations. The mutation spectrum of AGL gene in the multi-ethnic Malaysian population is still unknown. Objective: The present study seeks to determine the mutation spectrum of the AGL gene in Malaysian population. Methods: A total of eleven patients (eight Malay, two Chinese and one Bajau) were investigated. Genomic DNA was extracted and subsequently the AGL gene was amplified using specific primers and sequenced. Mutations found were screened in 150 healthy control samples either by restriction enzyme digestion assay or TaqMan® SNP Genotyping assay. Results: We identified six unreported mutations (c.1423+1G>T, c.2914_2915delAA, c.3814_3815delAG, c.4333T>G, c.4490G>A, c.4531_4534delTGTC) along with three previously reported mutations (c.99C>T, c.1783C>T, c.2681+1G>A). One of the six unreported mutation causes abnormal splicing and results in retention of intron 12 of the mature transcript, while another is a termination read-through. One of the reported mutation c.2681+1G>A was recurrently found in the Malay patients (n = 7 alleles; 31.8%). Conclusion: The mutation spectrum of the AGL gene in Malaysian patients has shown considerable heterogeneity, and all unreported mutations were absent in all 150 healthy control samples tested. © 2019, The Genetics Society of Korea.